Enfermedad periodontal, su terapia: un reto - Maita Véliz, Luis Vidal (2006)
The diagnosis and treatmnet of the periodontal disease must be an objetive in the dental practice. To reach this purpose, the patient must have high motivation and the dentist must work in the maintenance periodontal therapy; this leads to have healthy periodontal tissue- specially the bone- for ever and the teeth also.